Analysis of the nuclear potential for heavy-ion systems through large-angle quasi-elastic scattering - Inche Ibrahim, Mohd Lukman; Zamrun, Muhammad; Abu Kassim, Hasan (American Physical Society, 2013)
A study on the surface diffuseness parameter of the nuclear potential for the reactions of 208Pb with 48Ti, 54Cr, 56Fe, 64Ni, and 70Zn is performed using large-angle quasi-elastic scattering experimental data. Diffuseness parameters that are considerably lower than the standard value of around 0.63 fm are required in order to fit the experimental data at deep sub-barrier energies, except for the 54Cr + 208Pb system, where the required diffuseness parameter is in satisfactory agreement with (but still lower than) the standard value. Furthermore, when the energies of the experimental data used in the fittings are increased from the deep sub-barrier region to the energies closer to the Coulomb barrier height, the best fitted diffuseness parameters also increase. The increase in the obtained diffuseness parameters as the energies are increased also seems to have a possible tendency to be a function of the charge product of the target and projectile nuclei. We find that the phenomenon of threshold anomaly might explain our findings here. The increase in the diffuseness parameters could also due to dynamical effects, for example, due to neutron movements.